Poverty-proofing the school day. (28th February 2019) - Lee-Potter, Emma
Abstract : The one place where it can be particularly miserable to be poor is in school. The Poverty Proofing the School Day initiative seeks to help schools identify and tackle the many financial barriers that prevent pupils from fully partaking in school life.Emma Lee-Potter explains